(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2018)
The impacts of petroleum hydrocarbon pollution on macrobenthic of Oluasiri River in the Niger Delta of Nigeria was undertaken between January 2013 and June 2013, to assess the composition and distribution of benthic organisms. The diversity of benthic fauna was poor, only eleven (11) benthic macrofauna species in four classes polychaeta, mollusca, crustacean and oligochaeta were identified. The highest number of 218 benthic fauna were recorded in the month of February, followed by June (190), January (134), April (128), March (117) and May (112) respectively. The polychaetes population were the dominant class, comprising Neathes fucata, Neresis sp. and Nepthys hombergi. There was variation in the density of macro invertebrates from station 5 to station 1, the highest density was in station 5 (279), followed in decreasing order in the subsequent stations. Stations 4 (200), 3(188), 2(131) while the least species abundance of the identified benthic fauna was recorded in station 1 (98). Macrobenthic infauna distributed per station were significant (p > 0.05) in Oluasiri River except Neresis sp. and Tubicifid sp. Paehymelania aurita, Pachymelania bryonensis and Neritina oweniana were completely absence in stations 1 and 2 and negligible in station 3 (0.0 ± 0C, 0.0 ± 0C and 0.67 ± 0.21C) respectively. It was recommended that there should be private and government partnership sensitization program for the public, on the health and safety hazards of oil when it spills and oil producing communities should be more conscious of their safety and environment.